Perception of School Citizens about Violence against Students - Zuman Malaka; Bambang Satriya; Kridawati Sadhana (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
One of the social realities about violence against students at MTS Nurul Khoir Surabaya that attracts attention, namely violence in the form of